1990
DOI: 10.1002/ana.410270112
|View full text |Cite
|
Sign up to set email alerts
|

Naltrexone therapy of apnea in children with elevated cerebrospinal fluid β‐endorphin

Abstract: Previous studies have indicated increased immunoreactivity of the endogenous opioid peptide beta-endorphin in the cerebrospinal fluid (CSF) of infants under 2 years of age with apnea. To assess the role of endogenous opioids in the pathogenesis of apnea in children, the effect of oral treatment with the opioid antagonist naltrexone was studied in apneic infants, as well as in older apneic children, with demonstrated increases in CSF immunoreactive beta-endorphin (i-BE). In the 8 apneic infants with elevated i-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Children with apnoea and increased levels of BENDI in CSF have been successfully treated with the opioid antagonist, naltrexone [29]. Furthermore, certain types of apnoea can be triggered by emotional stimuli such as fear, anger and pain [39].…”
Section: Introductionmentioning
confidence: 99%
“…Children with apnoea and increased levels of BENDI in CSF have been successfully treated with the opioid antagonist, naltrexone [29]. Furthermore, certain types of apnoea can be triggered by emotional stimuli such as fear, anger and pain [39].…”
Section: Introductionmentioning
confidence: 99%
“…Children suffering from apnoeas, siblings of SID victims, and 50% of SID victims have increased levels of beta-endorphin immunoreactivity (BENDI) in CSF [12,26]. Children with apnoeas and an increased level of BENDI in CSF have been successfully treated with the opioid antagonist, naltrexone [13].…”
Section: Introductionmentioning
confidence: 99%
“…This lack of additive effects, and the similarity in response to nicotine and endotoxin might indicate the involvement of a final common pathway: Investigators at our institute have earlier demonstrated that CSF ß-endorphin prolongs apneas by laryngeal chemoreflex in piglets [28,29]. Infants with severe apnea, ALTE, and siblings of SIDS victims have higher levels of CSF ß-endorphin [30][31][32][33], although not in the newborn [34]. Increased CSF ß-endorphin is also found post-mortem in some SIDS victims [35][36][37].…”
Section: Discussionmentioning
confidence: 99%